Assessing the Influence of Diesel-Butanol Blends on Diesel Engine Performance and Emissions - Tomar, Suyash; Soni, Amrit (Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
This study aimed to assess the combustion, performance, and emission characteristics of diesel engines using diesel-oxygenate blends. Experimental investigations were conducted on a single cylinder four stroke direct injection water-cooled diesel engine using butanol blended fuels in different volume ratios. The results showed that brake thermal efficiency increased with increased butanol content, reduced CO emission levels at higher loads, and comparable NOx emissions with diesel-butanol blends to neat diesel at low loads. However, butanol showed the lowest smoke opacity at high engine loads compared to diesel fuel operation.